Evaluation of a new selective medium, BD BBL CHROMagar MRSA II, for detection of methicillin-resistant staphylococcus aureus in different specimens - Wendt, Constanze; Havill, N. L.; Chapin, K. C.; Boyce, J. M.; Dickenson, R.; Eigner, U.; Schütt, Sabine; Fahr, A. M. (Journal of clinical microbiology, 2010)
The sensitivity of screening for methicillin-resistant Staphylococcus aureus (MRSA) can be improved by adding other specimen sites to nares. We describe an evaluation of a new selective medium, BBL CHROMagar MRSA II (CMRSAII), for its ability to detect MRSA from different specimen types. CMRSAII is a chromogenic medium which incorporates cefoxitin for the detection of MRSA. A study was performed at four clinical laboratories with the following specimens: 1,446 respiratory, 694 stool, 1,275 skin, and 948 wound specimens and 688 blood culture bottles containing Gram-positive cocci. The recovery of MRSA on traditional culture media was compared to results with CMRSAII. S. aureus was tested by cefoxitin disk diffusion. CMRSAII was interpreted as positive for MRSA at 24 h (range, 18 to 28 h) based solely on the visualization of mauve-colored colonies and at 48 h (range, 36 to 52 h) based on detection of mauve colonies with subsequent confirmation as S. aureus (by coagulase or latex agglutination testing). MRSA was recovered more frequently on CMRSAII (89.8% at 24 h and 95.6% at 48 h) than on traditional culture plates (83.1% at 24 h and 79.8% at 48 h) for all specimen types combined (P < 0.001). The percent sensitivities of CMRSAII at 24- and 48-h reads, respectively, were 85.5 and 92.4% for respiratory specimens, 87.9% and 98.3% for stool specimens, 88.4% and 96.1% for skin specimens, 92.1% and 94.6% for wound specimens, and 100% and 100% for positive blood cultures. The specificity was 99.8% for respiratory specimens and 100% for all others. In conclusion, CMRSAII is a reliable screening medium for multiple specimen types.